Halt for Speaking - Hansun Waring; Carol Hoi Yee Lo (Social Interaction, 2024)
Conversation analytic (CA) research on multimodality has mostly focused on the “movement” rather than the “freezing” of such movement, except for a small body of work on gesture holds mostly in sign language and several European languages. Based on two large corpora of video-recorded family interactions and adult ESL classroom interactions in American English, this conversation analytic study demonstrates how halts of eating and drinking are carefully configured to preserve contiguity by facilitating completion and repair. Findings expand our understanding of the interdependence between multimodality and sequence organization within the larger context of managing multiactivity and materiality.